Pengaruh Kewirausahaan terhadap Kinerja Usahatani Tembakau di Kecamatan Gantiwarno Kabupaten Klaten - Sadjudi (Universitas Brawijaya, Indonesia, 2009)
This research is descriptive research and research of Explanative because to characteristic of variable and relation between variable. Evaluated from investigation type, this research is causality research with purpose to analyze causality between variable Population of this research is farmer of tobacco in District Of Gantiwarno Sub-Province of Klaten. Sample taken by using technique of purposive sampling which have type of quota sampling, from result of calculation obtained sample counted 100 responder. This Research variable consist of independent variable that is economic environment; physical environment; individual characteristic; and entrepreneurship. While dependent variable is farmer performance. Data collecting obtained to answer of questionnaire of responder as report documentation and sample and publication of relevant institute. Technique analyze data use Factor analysis, model Path Analyze , and model Analyze Regression. Result of research can be concluded that environmental Pattern influence of economics, environmental of physical, individual aspect and also entrepreneurship to performance of tobacco farmer, will be more benefit if relying on model Analyze Regression have Pennant, and also the existence of influence of Behavioral variable moderating of entrepreneurship. Bravery farmer of tobacco in setting mind on to account failure risk in finding technical and new modern technology moderating by individual behavior. Beneficial and Correct policy in fixed price, very influenced by condition of economics, amenity get capital or fund, emulation of effort which is healthy to be, supported by policy of duty, nicotine, and tar, and also industrial support of cigarette.